Women’s knowledge of the development and communication of children with Fetal Alcohol Syndrome (FAS) - Cybulska, Justyna; Zając, Ewelina (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2021)
The aim of the article is to analyze the results of surveys on women’s knowledge about FAS and its consequences for the development of a child’s speech and communication. 130 women between 18 and 50 years old took part in the survey. A significant proportion of the surveyed women are aware of the problems and consequences of Fetal Alcohol Syndrome caused by the mother’s alcohol consumption during pregnancy.